1997
DOI: 10.1021/om9701478
|View full text |Cite
|
Sign up to set email alerts
|

Application of S,N-Chelating Chiral Zinc Bis(aminoarenethiolates) as New Precursor Catalysts in the Enantioselective Addition of Dialkylzincs to Aldehydes

Abstract: A new enantiomerically pure S,N-chelated zinc bis(aminoarenethiolate), (R,R)-Zn(SC 6 H 4 C-(Me)HNMe 2-2) 2 ((R,R)-3b), has been synthesized by the reaction of the (R)-trimethylsilyl aminoarenethiolate species (R)-2b with ZnCl 2 in a 2:1 molar ratio. (R,R)-3b is an efficient catalyst for the addition of dialkylzinc compounds to aliphatic and aromatic aldehydes to give the corresponding secondary alcohols in nearly quantitative yields with optical purities of 69-99% ee under mild reaction conditions. Although ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
31
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…This topic has been reviewed recently. 1 Previously, we 4 and others 5 have shown that chiral o-aminoarenethiolates are excellent catalyst for the enantio-selective addition of dialkylzincs to aldehydes. It is thus a challenge to modify these catalyst in such a way that they become applicable in FBS.…”
mentioning
confidence: 96%
“…This topic has been reviewed recently. 1 Previously, we 4 and others 5 have shown that chiral o-aminoarenethiolates are excellent catalyst for the enantio-selective addition of dialkylzincs to aldehydes. It is thus a challenge to modify these catalyst in such a way that they become applicable in FBS.…”
mentioning
confidence: 96%
“…chiral bisphosphines, 2,3 which can be used as ligands in asymmetric catalysis. 4 The zinc-mediated addition of alkylzinc compounds to aldehydes, using chiral amino alcohols 5 or amino thiols 6,7 as catalyst precursors, affords the corresponding alcohols in high enantiomeric purity and high chemical yield. Recently, this methodology has been applied to the synthesis of C 2 -symmetric diols derived from terephthaldehyde and isophthaldehyde using (1S,2R)-DBNE 1 or (1S,2R)-PHONE as catalyst precursors.…”
mentioning
confidence: 99%
“…) and the aminoarenethiolate-based catalyst precursors (2-3b 6,7 ) (see Fig. 1) were applied in this reaction.…”
mentioning
confidence: 99%
See 2 more Smart Citations